PENGUATAN UMKM BATIK UNTUK PENINGKATAN EKONOMI LOKAL KOTA SUNGAI PENUH - Chatra, Afdhal (Jurnal Paradigma Ekonomika, 2024)
Batik MSMEs play a vital role in local economic development in Sungai Penuh City. Sungai Penuh’s distinctive batik features motifs inspired by local culture, making it a unique attraction with high market value. However, the development of this sector faces various challenges, such as limited capital, low adoption of technology, low production capacity, and restricted marketing networks. This study aims to analyze the current condition of batik MSMEs in Sungai Penuh City, formulate development strategies based on innovation, collaboration, and technology, and provide policy recommendations to local governments and other stakeholders. The analytical tools used include the IFE (Internal Factor Evaluation) matrix, EFE (External Factor Evaluation) matrix, IE (Internal-External) matrix, and SWOT analysis. The findings indicate that batik MSMEs possess a primary strength in their unique motifs rooted in local culture but face significant challenges in production capacity, marketing, and capital. Major opportunities lie in digital markets, government policy support, and strategic partnerships. Based on the IE matrix, batik MSMEs are positioned in a "grow and develop" category, requiring intensive strategies such as market penetration, market development, and product innovation.